Effects of pH soaking solutions and hypoxia/anaerobic treament on GABA accumulation in germinated mung bean - Trung, Truong Nhat; Tuong Danh, Nguyen; Thi Anh Dao, Dong (Vietnam Journal of Science and Technology, 2017)
This study investigated the accumulation of γ-aminobutyric acid (GABA) in mung bean sprouts (Vigna Radiata L.) during germination under hypoxia/anaerobic conditions. Raw mung bean seeds were soaked in water at 35oC for 8 hours, dried and germinated under aerobic or hypoxia/anaerobic conditions at 35oC or 40oC for 0, 6, 12, 24, 36 and 48 hours. Free amino acid and GABA contents were measured during the course of germination. Effect of soaking pH (5.3, 6.3 and 7.3) on GABA content of germinated mung beans under hypoxia/anaerobic condition was also investigated. The other objective of this study was to optimize the culture conditions of GABA production in germinated mung bean. A significant increase (p < 0.05) of GABA content was found in mung bean samples germinated under hypoxia/anaerobic condition. As this result, the combination of soaking pH 6.3 and 12 hour germination at 35oC was found to yield the highest GABA content (1519.07±19.58ppm). This figure was 1.41 times as high as the content in aerobic condition and 25.32 times as high as the analysis of the raw mung beans. And experimental analysis showed that the optimal condition with aeration treatment for GABA accumulation in germinated mung bean was at a temperature of 36.6oC, time of 14.5 h and a pH value of 5.83; the highest GABA yield was 1638.67ppm, which was 27.77 times higher than raw seeds. In conclusion, germinated mung bean is a good source of GABA and hypoxia/anaerobic condition in combination with soaking pH, germination time and temperature can increase significantly GABA content in germinated mung beans.